Implementation of Naïve Bayes and K-NN Algorithms in Diagnosing Stunting in Children - Wulan Widhari; Agung Triayudi; Ratih Titi Komala Sari (CV. Media Digital Publikasi Indonesia, 2024)
Indonesia faces a huge potential risk of stunting, as revealed in the Indonesian Nutrition Status Analysis according to 2022 data, the stunting rate reached 24.22% in 514 districts / cities throughout Indonesia. To prevent stunting in children, early detection can be done. This research was conducted to compare the performance of two algorithms Naive Bayes and K-NN to predict stunting cases in children, to get a better picture of how classification algorithms predict stunting cases with a better level of accuracy and responsiveness, comparison experiments of several algorithms are needed using specific datasets to develop an optimal classification model. Based on the results of performance testing on the K-Nearest Neighbor and Naive Bayes methods in testing the performance of accuracy, precision, recall, and f1-score, the results of performance testing on the naïve bayes method obtained performance values on 30% testing data are accuracy of 71%, precision 71%, recall 76%, and f1-score 73%. The performance results of the K-NN method using the euclidean distance measurement obtained the best performance value, namely accuracy of 97%, precision of 98%, recall of 96%, f1-score of 97% at a value of k = 3. Based on the performance results of the comparison of the Naive Bayes and K-NN methods, it shows that the best classification method on the stunting dataset is the K-NN method because it gets better performance than the Naive Bayes method.